Sociocultural Attitudes Towards Appearance Questionnaire-4: Psychometric properties among a French clinical eating disorder sample and normative comparisons. (January 2021) - Rodgers, Rachel Rachel F.; Schaefer, Lauren M.; Seneque, Maude; Alacreu-Crespo, Adrián; Moreno-Padilla, Maria; Courtet, Philippe; Thompson, J. Kevin; Guillaume, F.L. Sebastien
Abstract: Although the Sociocultural Attitudes Towards Appearance Questionnaire-4 (SATAQ-4) has been shown to be a reliable and valid tool for assessing appearance pressures and appearance ideal internalization among French college students, to date its psychometric properties among French clinical populations have not been examined. The aim of this study was to evaluate the factor structure, reliability, and validity of the SATAQ-4 among a French female clinical eating disorder sample, and to compare the mean SATAQ-4 scores from this clinical sample to previously published means observed among French female college women. The current sample included 192 French women consecutively recruited from an outpatient eating disorders unit in France. Participants completed the SATAQ-4, as well as validated measures of body image and eating pathology. Confirmatory factor analysis revealed that the original 22-item five-factor solution provided less than adequate fit to the data. In contrast, the reduced 20-item five-factor solution identified among French college students provided a good fit to the data. The SATAQ-4 subscales generally exhibited moderate positive associations with convergent measures of body image and eating disturbance, consistent with expectations. Differences in SATAQ-4 subscale means across diagnostic groups were observed. In addition, the clinical group reported higher scores on the Internalization: Thin/Low Body Fat and Internalization: Muscular/Athletic subscales compared to a non-clinical French sample. Findings support the SATAQ-4 as a valuable tool for assessing sociocultural influences on body image and eating concerns among French women with eating disorders. Highlights: The French SATAQ4 revealed good psychometric properties in a clinical sample. The clinical-population factor structure was identical to that in the French general population. SATAQ-4 subscales exhibited moderate positive associations with convergent measures. Differences in SATAQ-4 subscale means across diagnostic groups were observed.